2012
DOI: 10.1371/journal.pone.0051027
|View full text |Cite
|
Sign up to set email alerts
|

A Veritable Menagerie of Heritable Bacteria from Ants, Butterflies, and Beyond: Broad Molecular Surveys and a Systematic Review

Abstract: Maternally transmitted bacteria have been important players in the evolution of insects and other arthropods, affecting their nutrition, defense, development, and reproduction. Wolbachia are the best studied among these and typically the most prevalent. While several other bacteria have independently evolved a heritable lifestyle, less is known about their host ranges. Moreover, most groups of insects have not had their heritable microflora systematically surveyed across a broad range of their taxonomic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 95 publications
8
113
2
Order By: Relevance
“…3b), in accordance with a statistical analysis reported by Hilgenboecker et al (54). Despite several reports about the distribution of intracellular symbionts that regulate host reproduction, such as Wolbachia, Spiroplasma, and "Candidatus Cardinium" (53)(54)(55)(56)(58)(59)(60), there are few studies addressing the broad distribution of hostspecific bacteria from a wide range of insect hosts.…”
Section: Figsupporting
confidence: 82%
“…3b), in accordance with a statistical analysis reported by Hilgenboecker et al (54). Despite several reports about the distribution of intracellular symbionts that regulate host reproduction, such as Wolbachia, Spiroplasma, and "Candidatus Cardinium" (53)(54)(55)(56)(58)(59)(60), there are few studies addressing the broad distribution of hostspecific bacteria from a wide range of insect hosts.…”
Section: Figsupporting
confidence: 82%
“…Both the DGGE and pyrosequencing screens also identified Arsenophonus as an abundant symbiont in O. albicinctus. Arsenophonus, a very common facultative inherited symbiont of terrestrial arthropods, was found to infect ϳ4% of arthropod species in a recent large screening study of 136 species in 15 orders (3); Hemiptera, including leafhoppers, are commonly infected (3,40).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that symbiont infection frequency might vary predictably with host biology [1,3,6,7,[9][10][11][12][13][14][15][16]. For example, two distinct arguments predict that symbionts should be more common in host taxa that are species rich.…”
Section: Introductionmentioning
confidence: 99%